2006
DOI: 10.1007/s10549-006-9179-y
|View full text |Cite
|
Sign up to set email alerts
|

Post-diagnosis weight gain and breast cancer recurrence in women with early stage breast cancer

Abstract: PURPOSE: To examine whether weight gain after diagnosis of breast cancer affects the risk of breast cancer recurrence.PATIENT AND METHODS: Patients included 3215 women diagnosed with early stage breast cancer (Stage I > 1 cm., II, and IIIA) who were enrolled either in an observational cohort of breast cancer survivors or were part of the comparison group of a dietary intervention trial to prevent breast cancer recurrence. We computed weight change from 1 yr prior to diagnosis to study enrollment. Delayed entry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
121
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 132 publications
(134 citation statements)
references
References 35 publications
(41 reference statements)
11
121
1
Order By: Relevance
“…These findings were especially apparent in women who never smoked, among women with earlier stage disease or those who were normal weight before diagnosis [33]. In contrast, a collaborative effort between the LACE study and the WHEL study, did not observe an association between post-diagnosis weight gain and recurrence risk in the first 5-7 years postdiagnosis [34].…”
Section: Biological Mechanismmentioning
confidence: 86%
“…These findings were especially apparent in women who never smoked, among women with earlier stage disease or those who were normal weight before diagnosis [33]. In contrast, a collaborative effort between the LACE study and the WHEL study, did not observe an association between post-diagnosis weight gain and recurrence risk in the first 5-7 years postdiagnosis [34].…”
Section: Biological Mechanismmentioning
confidence: 86%
“…Only a few studies have addressed weight change after breast cancer diagnosis, and results have been inconsistent (25,(36)(37)(38). Whereas the Nurses' Health Study (n = 5,204) reported an increased risk of breast cancer death with increasing weight gain after breast cancer diagnosis (25), other studies have failed to find an association between postdiagnostic weight gain and prognosis (38,39). Thus, it is not clear whether weight gain after diagnosis influences mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported that chemotherapy is associated with weight gain [7][8][9][10][11]. Weight gain may have long-term consequences because it can lead to a higher risk of developing cardiovascular disease, diabetes and disease recurrence in survivors of breast cancer [12][13][14][15], and at least half of the patients experience unhappiness concerning their body changes and altered physical appearance, which negatively affected their quality of life [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%